High prevalence of HPV in non-cervical sites of women with abnormal cervical cytology - Vaughan Katie; Ball Siolian LR; Winder David M; Kitson Sarah; Grignon Anne-Laure; Crawford Robin; Stanley Margaret A; Sterling Jane C; Goon Peter KC (BMC Cancer, 2011)
Abstract Background Human papillomaviruses (HPV) are causally associated with ano-genital and a subset of head and neck cancers. Rising incidence of HPV+ anal cancers and head and neck cancers have now been demonstrated in the developed world over the last decade. The majority of published data on HPV prevalence at the anal and oro-pharyngeal sites are from studies of higher-risk populations. There is a paucity of data on the prevalence of HPV at non-cervical sites in lower risk, non-HIV+ women and this study was designed to provide initial pilot data on a population of women recalled for colposcopy as part of the UK cervical screening programme. Methods 100 non-HIV+ women with abnormal cervical cytology, attending clinic for colposcopic examination were recruited. Swabs from the oro-pharyngeal, anal and cervical sites were taken and DNA extracted. HPV detection and genotyping were performed using a standardised, commercially available PCR-line blot assay, which is used to genotype 37 HPV subtypes known to infect the ano-genital and oro-pharyngeal areas. Strict sampling and laboratory precautions were taken to prevent cross-contamination. Results There was a very high prevalence of HPV infection at all three sites: 96.0%, 91.4% and 92.4% at the cervix, anus and oro-pharynx, respectively. Multiple HPV subtype infections were dominant at all 3 mucosal sites. At least one or more HR genotype was present at both the cervix/anus in 39/52 (75.0%) patients; both the cervix/oro-pharynx in 48/56 (85.7%) patients; and both the anus/oro-pharynx in 39/52 (75.0%) patients. HPV 16 infection was highly dominant across all mucosal sites, with over a 2-fold increase over the next most prevalent subtype (HPV 31). Conclusions Women with abnormal smears have widespread infection with high-risk HPV at the cervical, anal and oro-pharyngeal mucosal sites and may represent a higher risk population for HPV disease in the future.